The Changing Nature of the Australian Electricity Industry. Issue 2 (28th February 2017) - Nelson, Tim; Bashir, Stephanie; McCracken‐Hewson, Eleanor; Pierce, Michael
Abstract : The electricity supply industry has historically offered a homogenous good supplied via economically regulated transmission and distribution networks. Competition was introduced into the contestable generation and retail supply chain components as part of the 1990s Hilmer reform process. After a century of incremental technological developments, the industry is now being transformed by new distributed energy technologies and a global focus on reducing anthropogenic greenhouse gas emissions. Policy‐makers did not anticipate these changes. A number of key reforms are likely to be required. These include: assessing whether the return on capital provided to network operators is appropriate given changing economic conditions; determining the role of competition in the provision of "behind the meter" energy services; and integration of climate change policy with wholesale energy market design.